2011
DOI: 10.1108/17410391111097447
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of continuance intentions towards e‐shopping: the case of Saudi Arabia

Abstract: Purpose-The purpose of this study is to clarify the theoretical problem and identify factors that could explain the level of continuance intentions towards e-shopping. It aims to propose a revised technology acceptance model that integrates expectation confirmation theory to measure age differences with regard to continuance intentions towards e-shopping in Saudi Arabia. Design/methodology/approach-The sample (n=465) consists of 68.8 per cent women and 31.4 per cent men, 348 younger than 35 years old and 117 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 80 publications
9
77
1
Order By: Relevance
“…Al-maghrabi, Dennis, and Halliday (2011) said that if the value of products from new technology could be achieved, it will lead someone to have positive behaviour. Internet is a new technology in food purchasing, it means that the theory could be applied.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Al-maghrabi, Dennis, and Halliday (2011) said that if the value of products from new technology could be achieved, it will lead someone to have positive behaviour. Internet is a new technology in food purchasing, it means that the theory could be applied.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Ball et al (2004) found that PV has a direct impact on SAT while Bolton et al (2003) found value mediates the effects of both SAT and behavioural intentions in the B2B context. In addition, Wu et al, (2014) found PV is positively related to the ORI while Wang (2013) hypothesis that PV positively influence brand preference, and in return, purchase intention (Zeithaml, 1988), key retail outcome , online shopping continuance intention (Al-Maghrabi et al, 2011) and store loyalty (Sirohi et al, 1998).Therefore, we hypothesize that:…”
Section: Pv and Orimentioning
confidence: 90%
“…PU refers to individual total view that online retailing will improve the result of shopping (Dennis et al, 2009). PU has been found to be the strongest predictor of intention in TAM and continues to be the strongest predictor of ORI (Al-Maghrabi et al, 2011). It has also been found to influence attitude towards an online retailer (Lee et al, 2006), online stock trading (Ramayah et al, 2009) and ORI (Zhang et al, 2011).…”
Section: User Perceptions Of Online Retail Attributesmentioning
confidence: 99%
“…In addition, many researchers stated that ECM model can be employed to look into e-commerce better than other existing models and theories, e.g. (1,(17)(18)(19)(20)(21)(22). Hence, in the same way, many studies concentrated on user satisfaction, and many influential constructs have been brought into the original ECM to extend the model, and in order to explain the power in the continuance usage intention.…”
Section: Review Of Literature On Continuance Usagementioning
confidence: 99%